2020
DOI: 10.21203/rs.3.rs-34492/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Covid-19 in the second half of pregnancy: prevalence and clinical relevance

Abstract: Evidence on the prevalence and outcome of Covid-19 in pregnancy is yet inconclusive. To draw more information on this issue, we prospectively recruited 315 consecutive women delivering in a referral hospital located in Lombardy, Italy and evaluated the proportion of women who had Covid-19 in pregnancy. All recruited subjects underwent a nasopharyngeal swab to assess the presence of Sars-Cov-2 using Real-time PCR. In addition, two different type of antibodies for the virus were evaluated in peripheral blood, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Reportedly, 70% of those women had high C-reactive protein, 59% had lymphocytopenia, and 91% delivered by C-section. In another study, symptoms including fever, cough, shortness of breath, and anosmia were found to be significantly associated with COVID-19 in pregnancy [18].…”
Section: Discussionmentioning
confidence: 90%
“…Reportedly, 70% of those women had high C-reactive protein, 59% had lymphocytopenia, and 91% delivered by C-section. In another study, symptoms including fever, cough, shortness of breath, and anosmia were found to be significantly associated with COVID-19 in pregnancy [18].…”
Section: Discussionmentioning
confidence: 90%
“…14 Another study found a significant relationship between COVID-19 in pregnancy and symptoms such as fever, cough, shortness of breath, and anosmia. 15 When it is considered that elevated D-dimer levels are typical in pregnancy, it remains uncertain which cut-off value shows a poor prognosis. 13 Other than those who are pregnant, the anticoagulation results of coagulopathic, septic patients improve.…”
Section: Pcr Test Positive (N=50mentioning
confidence: 99%